Hidden stories of caregivers with children living with sickle cell disease in Uganda: Experiences, coping strategies and outcomes - Isaac Alinda; Lydia Kabiri; Hadad Ssebagala (PLoS ONE, 2025)
Background Sickle Cell Disease (SCD) poses a substantial public health challenge in Uganda, exhibiting distinct regional variations in prevalence. The Uganda Sickle Cell Surveillance Study has estimated an overall SCD prevalence of 13.3%. Notably, this prevalence varies significantly across the country’s regions, reaching its highest in the northern region at 22.2% and it’s lowest in the central region at 5.3%. This variation reflects the diverse impact of SCD and underscores the need for a comprehensive understanding of its regional implications. SCD places substantial physical, social, and psychological burdens on caregivers, potentially leading to heightened parental stress. However, limited research has focused on the daily challenges and experiences of SCD caregivers, despite evidence showing the detrimental impact on their emotional well-being, personal lives, employability, and socioeconomic status. This study explored the undisclosed struggles of Ugandan caregivers tending to children with SCD, uncovering their coping strategies and subsequent outcomes. Methods In June and July 2023, we conducted in-depth interviews with caregivers at Mulago sickle cell clinic after obtaining their informed consent. An interview guide was used as the primary data collection tool, with interviews lasting 30–45 minutes. Twelve participants were recruited, ensuring comprehensive data collection by following the data saturation principle. We analyzed the collected data using open coding. Results Three key themes emerged: caregiver experiences, coping strategies, and outcomes. Initially, caregivers grappled with confusion and uncertainty before a formal diagnosis. Financial strain and inadequate support posed persistent challenges, affecting their emotional well-being. Coping strategies varied, encompassing traditional remedies and modern medical treatments for symptom relief. Coping outcomes were complex, reflecting caregivers’ resilience alongside substantial emotional distress and sleep disturbances. The substantial financial burden further exacerbated their overall well-being. Conclusion Elevating awareness and knowledge about sickle cell disease within communities is essential. Such awareness can empower caregivers of children living with sickle cell disease, promoting emotional resilience and mitigating family disruptions.